First person - Celia Cordero-Sanchez (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Celia Cordero-Sanchez is joint first author on 'A luminal EF-hand mutation in STIM1 in mice causes the clinical hallmarks of tubular aggregate myopathy', published in DMM. Celia is a PhD student in the lab of Armando Genazzani at the University of Piemonte Orientale, investigating a mouse model of tubular aggregate myopathy.